Pengabdian Mahasiswa UPR Melalui Pengolahan Puding Buah sebagai Solusi Mengatasi Stunting di Desa Samba Danum - Ira Veronika Girsang; Duwi Tahlia Saputri; Reyssa Aurora Carolina; Mia Natalia; Muhammad Gustianda; Lina Wati; Ermita Pebriasi; Rindiyani Rindiyani; Melcy Melcy; Ilham Ilham; Rhyan Japarmen Bagas Kara; Kevin Keegan; Pedrick Pransvito Januar Febriantory; Ellydia Ludang (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2024)
Kuliah Kerja Nyata Tematik 2024 is an annual event at the University of Palangka Raya, where students are allowed to serve society especially people who live in the village, and experience real-life situations while applying their knowledge in KKN’s Programs to give real solutions for society. One of the KKN groups from the University of Palangka Raya assigned to Samba Danum Village, Central Katingan subdistrict found that Samba Danum village needs a solution to overcome stunting in children. Producing Fruit pudding with high-quality ingredients it is hoped to overcome stunting in Samba Danum village.